TP6.2.2 Multi-disciplinary interventions to increase utilisation of NELA scores and critical care involvement following emergency colorectal surgery. (28th October 2021) - Smith, Scott; Hodge, Katherine; Ying, Andrew; Swan, Rebecca; Von Maydell, Alexander; Ventham, Nicholas
Abstract: Aims: This audit aimed to assess pre-operative NELA risk score documentation and subsequent specialist peri-operative critical care involvement. Methods: This complete audit cycle retrospectively reviewed notes (electronic patient records, anaesthetic charts and CEPOD booking forms) of all patients undergoing emergency laparotomy between March and May 2019. The NELA score was calculated retrospectively if not documented. Following the initial audit, the following multi-disciplinary interventions were instituted: alteration of the physical CEPOD booking form to include NELA score (Surgical); a sticker added to anaesthetic charts to prompt NELA calculation (Anaesthetic), formal recording of NELA score during theatre brief (Theatre staff); and by increasing awareness of NELA via departmental education (All). The audit cycle was completed by reassessment between October and November 2020. Results: The initial cycle included 34 patients, with only 2 (6%) having a NELA documented. The repeat cycle included 35 patients, with 29 (83%) having a NELA documented. Regarding post-operative critical care admissions, both cycles found that 100% of patients with a NELA of ≥ 5%, were admitted to either surgical HDU or ICU (n = 17 in first cycle, n = 17 in second cycle). For those with a high-risk NELA of ≥ 10% (n = 11 in first cycle, n = 7 in second cycle), only 2 (18%) were admitted to ICU in the first cycle vs 7 (100%) in the second cycle. Conclusions: This complete audit cycle demonstrates improved NELA score calculation following institution of several multidisciplinary interventions. The improved NELA score uptake was associated with increased critical care review and admission to ITU in high-risk cases.